2004
DOI: 10.1158/1078-0432.ccr-03-0604
|View full text |Cite
|
Sign up to set email alerts
|

BRCA Mutations and Risk of Prostate Cancer in Ashkenazi Jews

Abstract: Purpose: The Breast Cancer Linkage Consortium and other family-based ascertainments have suggested that male carriers of BRCA mutations are at increased risk of prostate cancer. Several series looking at the frequency of BRCA mutations in unselected patients with prostate cancer have not confirmed this finding. To clarify this issue, we conducted a large case-control study.Experimental Design: Blood specimens from 251 unselected Ashkenazi men with prostate cancer were screened for the presence of one of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
106
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(115 citation statements)
references
References 25 publications
6
106
1
2
Order By: Relevance
“…It has been estimated that ,2% of this population carries at least one of these mutations. [77][78][79][80] Even in this population, the results of these epidemiological studies have been contradictory, but many of them were underpowered, due to small sample size or lack of covariate information. 22,[81][82][83][84][85][86] Another BRCA2 founder mutation that has been extensively studied is the Icelandic BRCA2 999del5 mutation.…”
Section: Discussionmentioning
confidence: 97%
“…It has been estimated that ,2% of this population carries at least one of these mutations. [77][78][79][80] Even in this population, the results of these epidemiological studies have been contradictory, but many of them were underpowered, due to small sample size or lack of covariate information. 22,[81][82][83][84][85][86] Another BRCA2 founder mutation that has been extensively studied is the Icelandic BRCA2 999del5 mutation.…”
Section: Discussionmentioning
confidence: 97%
“…Given that only one-half of the first-degree relatives are expected to be gene carriers, this corresponds to a relative risk of prostate cancer, given a BRCA2 mutation, of approximately five. Kirchoff et al (2004) tested 251 unselected Ashkenazi Jewish men with prostate cancer from the New York area for the two founder mutations in BRCA1 and the one in BRCA2. They also tested 1472 Ashkenazi controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, we estimate that o1% of early-onset prostate cancers in the general US Caucasian population can be attributed to these rare disease-associated BRCA2 mutations. British Journal of Cancer (2007) (BCLC, 1999;Johannsson et al, 1999;Eerola et al, 2001;Tulinius et al, 2002;Bermejo and Hemminki, 2004;van Asperen et al, 2005), kin-cohort studies of cancer incidence among relatives of population-based breast or ovarian cancer cases (Loman et al, 2003;Risch et al, 2006), as well as studies of populations who harbour founder BRCA2 mutations (Sigurdsson et al, 1997;Struewing et al, 1997, Kirchhoff et al, 2004 suggest that men who carry a diseaseassociated BRCA2 allele have an increased relative risk (RR) of prostate cancer (two-to five-fold elevation). Two of the family studies in which data were stratified on age at diagnosis of prostate cancer reported that the RR was even higher (seven-to eight-fold increase) in men diagnosed before age 65 years (BCLC, 1999;van Asperen et al, 2005).…”
mentioning
confidence: 99%